Intellectual property protection in the fashion industry under EU Intellectual property law - Ismailova, Anastasija (Riga Graduate School of Law, 2018)
The aim of this thesis is to analyse legal and practical issues which arise in case of intellectual property protection in the fashion industry within the European Union and to find possible solutions. Currently, fashion is a multi-million-dollar fast-growing industry that plays a significant role in the European economics. Due to the fact that the fashion industry needs constant changes, creations, innovations and amendments, intellectual property rights and its protection remains a cornerstone of the European fashion industry model. However, the common rules provided by the European Intellectual property law are sometimes not effective enough in order to protect designers from increasing piracy, as current legislation does not take into account the specific features of this industry. That is the reason why it is not clear if current legislation is able to provide adequate regulation and protection to the fast-moving fashion industry.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Intellectual property law; Fashion law